The role of interleukin-17 gene polymorphism (RS612242 C11139G) in the formation of the cryoglobulinemic syndrome in patients with chronic hepatitis C - Kalashnyk, K. V.; Riabokon, Yu. Yu.; Калашник, Кирило Вадимович; Рябоконь, Юрій Юрійович (My University, 2019)
Background. Chronic hepatitis C (CHC) is characterized by the development of extrahepatic symptom manifestations, which leads to an increased risk of mortality in these patients. Today, the factors contributing to the development of extrahepatic manifestations of CHC are being studied. Particular attention is paid to determining the clinical significance of cytokine gene polymorphism. Therefore, the aim of our work was study the role of interleukin-17 gene polymorphism (rs612242 C11139G) in the mixed cryoglobulinemia (MC) formation and manifestation of cryoglobulinemic syndrome in patients with chronic hepatitis C. Materials and methods. The study included 149 patients with CHC and 45 healthy people. Determination of single-nucleotide IL-17 gene polymorphism (rs 612242 C11139G) was performed by real-time polymerase chain reaction. Statistical processing was performed in program "STATISTICA for Windows 13" (StatSoft Inc., No. JPZ804I382130ARCN10-J).Results. We found that most often in patients with CHC (140 - 94.0%) and in healthy people (39 - 86.7%) was detected СС-genotype. It was found that the GG genotype was found to be significantly more likely in healthy subjects (χ2=20.5, p<0.0001). It was determined that patients with MC were significantly more likely to have a CC-genotype compared with healthy people (χ2=5.08, p<0.05), but the frequency of detection of this genotype was not statistically different compared with patients without MC (p>0.05). In patients with CHC carriers of the CC genotype of the IL-17 gene polymorphism significantly more likely (p<0.05), clinical signs associated with MC, namely weakness (65.6% vs. 40.0%), arthralgia (58.9% vs. 30.0%), vasculitis (14.4% vs. 2.0%) with the formation of the Meltzer’s triad (14.4% vs. no formation). It was showed that type 2 diabetes was significantly more likely to be detected in patients without MC (χ2=5.52, p<0.05). Conclusion. Allele C of the IL-17 gene polymorphism has an effect on the chronicity of hepatitis C according to a multiplicative model of inheritance. The CC-genotype plays a role in the formation of HCV-associated MC. Weakness, arthralgia and vasculitis with the formation of the Meltzer’s triad are the most common manifestations of cryoglobulinemic syndrome.
Keywords: chronic hepatitis C; HCV; Genetic Polymorphism; interleukin-17; cryoglobulinemia